Effects of Acute, Profound Hypoxia on Healthy Humans: Implications for Safety of Tests Evaluating Pulse Oximetry or Tissue Oximetry Performance. (January 2017) - Bickler, Philip E.; Feiner, John R.; Lipnick, Michael S.; Batchelder, Paul; MacLeod, David B.; Severinghaus, John W.
Abstract : Extended periods of oxygen deprivation can produce acidosis, inflammation, energy failure, cell stress, or cell death. However, brief profound hypoxia (here defined as SaO2 50%–70% for approximately 10 minutes) is not associated with cardiovascular compromise and is tolerated by healthy humans without apparent ill effects. In contrast, chronic hypoxia induces a suite of adaptations and stresses that can result in either increased tolerance of hypoxia or disease, as in adaptation to altitude or in the syndrome of chronic mountain sickness. In healthy humans, brief profound hypoxia produces increased minute ventilation and increased cardiac output, but little or no alteration in blood chemistry. Central nervous system effects of acute profound hypoxia include transiently decreased cognitive performance, based on alterations in attention brought about by interruptions of frontal/central cerebral connectivity. However, provided there is no decrease in cardiac output or ischemia, brief profound hypoxemia in healthy humans is well tolerated without evidence of acidosis or lasting cognitive impairment. Abstract : Published ahead of print August 12, 2016.